A Mapping Review of Existing Tools to Assess Physical Qualities of Manual Wheelchair Users - Corentin Barthod; Jade Berthiaume; Marie-Ève Schmouth; Joanie Bédard; François Routhier; Krista L. Best (Disabilities, 2025)
Background: Assessment of physical competencies is one way to enhance uptake and maintain participation in a leisure-time physical activity (LTPA) for manual wheelchair (MWC) users. Weineck’s model explains physical competencies through eight physical qualities. The use of this model may influence MWC users’ motivation for participation in LTPA. The aim of this study was to identify and categorize existing assessment tools designed for MWC users of physical qualities (strength, speed, power, muscular endurance, cardiovascular endurance, balance, and flexibility). Methods: A mapping review was conducted following the “Preferred reporting items for systematic reviews and meta-analyses (PRISMA)” guidelines. Two reviewers selected articles that documented assessment tools for the physical qualities of MWC users. Tools were extracted from each article to categorize them in a list. Results: A total of 149 articles that contained assessments of physical qualities were included in the review. A total of 97 assessment tools were extracted and categorized according to the eight physical qualities. Conclusions: These assessments are categorized into physical qualities that would facilitate the creation of test batteries aimed at assessing physical qualities in MWC users. This study is the first step in the construction of a test battery to assess the physical qualities of MWC users.